Divergent performance outcomes following resistance training using repetition maximums or relative intensity - Carroll, K. M.; Bernards, J. R.; Bazyler, C. D.; Taber, C. B.; Stuart, C. A.; DeWeese, B. H.; Sato, K.; Stone, M. H. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To compare repetition maximum (RM) to relative intensity using sets and repetitions (RISR) resistance training on measures of training load, vertical jump, and force production in well-trained lifters. Methods: Fifteen well-trained (isometric peak force = 4403.61 [664.69] N, mean [SD]) males underwent resistance training 3 d/wk for 10 wk in either an RM group (n = 8) or RISR group (n = 7). Weeks 8 to 10 consisted of a tapering period for both groups. The RM group achieved a relative maximum each day, whereas the RISR group trained based on percentages. Testing at 5 time points included unweighted (<1 kg) and 20-kg squat jumps, countermovement jumps, and isometric midthigh pulls. Mixed-design analyses of variance and effect size using Hedge's g were used to assess within- and between-groups alterations. Results: Moderate between-groups effect sizes were observed for all squat-jump and countermovement-jump conditions supporting the RISR group (g = 0.76-1.07). A small between-groups effect size supported RISR for allometrically scaled isometric peak force (g = 0.20). Large and moderate between-groups effect sizes supported RISR for rate of force development from 0 to 50 ms (g = 1.25) and 0 to 100 ms (g = 0.89). Weekly volume load displacement was not different between groups (P > .05); however, training strain was statistically greater in the RM group (P < .05). Conclusions: Overall, this study demonstrated that RISR training yielded greater improvements in vertical jump, rate of force development, and maximal strength compared with RM training, which may be explained partly by differences in the imposed training stress and the use of failure/nonfailure training in a well-trained population.